2017
DOI: 10.4094/chnr.2017.23.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Perception, Mental Health, and Weight Control Behavior in Normal Weight Adolescents: Based on the Korea National Health and Nutrition Examination Survey 2013-2015

Abstract: Background: Distorted body image plays a significant role in the development of obesity, eating problems, and eating disorders. The aim of this study was to investigate the relationship between distorted body image and lifestyle among Japanese adolescent boys and girls. Methods: Subjects were 1731 seventh graders (age 12-13 years) from the Ina-town's junior high schools, Japan, from [2005][2006][2007][2008][2009]. The height and weight of each subject were measured. Childhood underweight, overweight, and obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Adolescents' values and attitudes toward their appearance are easily influenced by the mass media or their peer groups. Additionally, as this study's results have been supported by studies stating that even non-obese adolescents are highly preoccupied with their appearance, such as erroneously recognizing their body type as being obese, it shows that the betweenness centrality of "appearance" is particularly high in centrality analysis [24,32]. Disordered weight control behaviors should be considered when developing education programs to establish desirable weight control, given their prevalence among Korean adolescents [33], and their association with stress and depressive symptoms [24,34].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Adolescents' values and attitudes toward their appearance are easily influenced by the mass media or their peer groups. Additionally, as this study's results have been supported by studies stating that even non-obese adolescents are highly preoccupied with their appearance, such as erroneously recognizing their body type as being obese, it shows that the betweenness centrality of "appearance" is particularly high in centrality analysis [24,32]. Disordered weight control behaviors should be considered when developing education programs to establish desirable weight control, given their prevalence among Korean adolescents [33], and their association with stress and depressive symptoms [24,34].…”
Section: Discussionsupporting
confidence: 75%
“…For keyword selection, it is desirable to select the most appropriate word for the research topic, while referring to the opinions of experts [ 24 ]. Therefore, in this study, the top 50 words were selected based on their TF-IDF values, which reflected the opinions of a high school counselor, public health teacher, and network analysis expert.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic database searches identified 10,398 unique records, an additional 41 articles were suggested by authors, or were identified in the reference lists of eligible articles or in supplementary searches. Full text review of 381 articles was conducted, which yielded 32 studies that were eligible for inclusion in the present review (listed in Appendix F, Supplemental Materials; Armstrong et al, 2014;ter Bogt et al, 2006;Brown and Blanton, 2002;Byeon, 2013;Byeon, 2015;Daly et al, 2017;Eaton et al, 2005;Frisco et al, 2010;Gaskin et al, 2013;Jansen et al, 2008;Kim, 2011;Kim et al, 2009;Kim, Kim, Cho, & Cho, 2008;Kinoshita et al, 2012;Lee, 2017;Lee, Seo, Shim, & Lee, 2015;Lenhart et al, 2011;Lo et al, 2009;Lo et al, 2011;Roberts & Duong, 2013;Schiefelbein et al, 2012;Seo & Lee, 2013;Shin et al, 2015;Swahn et al, 2009;Thurston et al, 2017;Ting et al, 2012;Xie et al, 2006;Yuan, 2007Yuan, , 2012Zeller et al, 2013;Zhao et al, 2012). From those studies, 110 eligible effect sizes were extracted or calculated (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%